Modelling the evolution of microstructure and transport properties of cement pastes under conditions of accelerated leaching. (15th July 2016) - Phung, Quoc Tri; Maes, Norbert; Jacques, Diederik; Perko, Janez; De Schutter, Geert; Ye, Guang
Highlights: A 1D diffusion-based model for accelerated leaching of pastes in NH4 NO3 solution is developed. The transport of both calcium and nitrate is considered. The model enables to predict the changes in μ-structure and transport properties due to leaching. Limestone filler reduces the degradation rate and changes in μ-structure and transport properties. C-S-H leaching considerably contributes to changes in μ-structure and transport properties. Abstract: Calcium leaching might be a significant degradation process in concrete and reinforced structures with an anticipated long-term service life such as nuclear waste disposal systems or large hydro structures (dams, bridges, water tanks). The leaching process is extremely slow under environmental conditions, which fosters the use of accelerated experimental approaches such as leaching in an ammonium nitrate (NH4 NO3 ) solution. In this paper, we develop a one-dimensional diffusion-based transport model with the purpose to predict the changes in microstructure and transport properties of saturated cement pastes in contact with a NH4 NO3 solution. The model helps to better understand the transient state of leaching which is difficult to observe by experimental work. The main new elements in this model are change in model configuration with extended solution domains; ability to predict the spatial profiles of diffusivity and permeability; including the effect on solubility of the spatial-temporal evolution of nitrate concentration; and including the effect of limestone addition to the cement paste of leaching kinetics. This model is based on macroscopic mass balances for Ca in aqueous and solid phases which are linked together by applying a variable solid-liquid Ca equilibrium curve. Besides the prediction of the leached depth, porosity increase, portlandite and C-S-H contents, and the amount of leached Ca, the model also enables to estimate the variation of permeability and diffusivity over the domain at different immersion periods in NH4 NO3 solution. The model is verified by accelerated leaching experiments in 6 mol/l NH4 NO3 solution on CEM I cement pastes with/without limestone fillers. Verification with experimental results shows a good agreement.